Opening the black box of nomination committees: a case study of non-executive director selections in German supervisory boards. (10th July 2014) - Walther, Axel; Morner, Michèle
One important pre-requisite for the functioning of supervisory boards is the selection of adequate members. Accordingly, corporate governance codes recommend the professionalisation of the board selection process through the establishment of nomination committees. These committees should carry out two principal tasks: 1) drawing up appropriate requirement profiles; 2) rationally structuring the selection process. Analysing in-depth interviews with 27 nomination committees' members of twelve German supervisory boards, we show that not all nomination committees fulfil these tasks satisfactorily; sometimes they merely act symbolically and rationalise decisions already taken by CEOs or main shareholders ex-post. Overall we succeed in identifying three prototypical nomination committees – active, consultative, and box-ticking – and show their impact on the board selection process.